PENGUASAAN TANAH OLEH ORANG ASING DIINDONESIA SETELAH DIUNDANGKANNYAUNDANG-UNDANG NOMOR: 5 TAHUN 1960 TENTANG PERATURAN DASAR POKOK-POKOK AGRARIA - I Gede Sumerta (Kerta Dyatmika, 2021)
Abstract The issue of land rights is a central issue in our agrarian law system. With the advancement of tourism, visits from foreign tourists who come to Bali and supported by direct flight transportation to Bali, many foreign nationals come to Bali for various purposes including for vacation, vacation while doing business, work, learn culture, research and so on. , so that some of them stay in Bali for a few days and some for a long period of time and at the same time open a business. Furthermore, the authors are interested in further research on Land Ownership by Foreigners after the promulgation of the 1960 LoGA. The formulation of the problem in this study is whether foreigners can control land with property rights in Indonesia based on the 1960 LoGA and what are the requirements and procedures so that foreigners can control land in Indonesia based on the 1960 LoGA? The type of research used in this research is normative legal research which is also known as normative juridical, which discusses the doctrines contained in legal science, which aims to find legal principles and positive legal doctrines that apply. The author chooses the type of normative research in writing. This is due to a conflict of legal norms in terms of Land Ownership by Foreigners based on Law Number: 5 of 1960 and the Implementation of Government Regulation Number 103 of 2015. The results of the study show the following conclusions: first, that foreigners can own land in Indonesia with Use Rights and Rights Rent. Second, foreigners can own land with usufructuary rights in accordance with the mechanism determined by the law, namely by going through the following process: 1) Delegation of rights first, then the sale and purchase process is carried out before the Land Deed Making Officer (PPAT) followed by land registration at Local land office; 2) The relinquishment of rights is first carried out by Indonesian citizens, then followed by registration of the application for rights at the local land office.